2022
DOI: 10.3389/fphar.2022.836573
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activity Correlates With Behavior Effects of Anti-Seizure Drugs Efficacy Using the Zebrafish Pentylenetetrazol Seizure Model

Abstract: Approximately 30% of patients with epilepsy do not achieve adequate seizure control through current anti-seizure drugs and treatment methods. Therefore, a critical need exists to efficiently screen anti-seizure drugs to enhance our ability to tailor treatment protocols and improve patient outcomes. The zebrafish pentylenetetrazol (PTZ) seizure model has become an increasingly popular screening paradigm for novel anti-seizure compounds. However, previous research using this model was variable due to differing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…In this experiment, the ZebVortrack system was used to evaluate a variety of antiseizure drugs, and the results showed that these antiseizure drugs could reduce the activity frequency of larval zebra sh and suppress the seizure-like behavior induced by PTZ, which is in accordance with previous reports [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 88%
“…In this experiment, the ZebVortrack system was used to evaluate a variety of antiseizure drugs, and the results showed that these antiseizure drugs could reduce the activity frequency of larval zebra sh and suppress the seizure-like behavior induced by PTZ, which is in accordance with previous reports [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to the findings of Afrikanova et al, who reported inconsistencies in locomotor behavior and electroencephalogram results [ 16 ], the study by Zhang et al revealed a harmonious reduction in both behavioral and neural activity, meticulously analyzed through electroencephalogram and GCaMP studies [ 19 ]. These nuanced observations contribute valuable insights into the multifaceted effects of TPM on zebrafish larvae, emphasizing the significance of considering developmental stages and exposure durations in elucidating the compound’s impact.…”
Section: Discussionmentioning
confidence: 98%
“…Examining the anticonvulsant properties of TPM, 7 dpf larvae exhibited suppressed seizure-like behavior following an 18 h incubation with a 200 μM dose. Intriguingly, this suppression did not extend to the total seizure duration in the electroencephalogram assay [ 16 ] Further insights from a separate study indicated that both prolonged incubation and acute exposure to TPM (200 μM) resulted in conspicuous reductions in locomotor activity in 7 dpf zebrafish [ 19 ]. In the PTZ-induced seizure model (10 mM), the total movement was significantly diminished in both TPM-pretreated and acutely exposed groups compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations